PENGELOLAAN PEMBELAJARAN PENDIDIKAN KESETARAAN PAKET B PADA PKBM HARAPAN BANGSA, KECAMATAN TAMBANG, KABUPATEN KAMPAR - Rizky kurniawan; Wilson Wilson; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this study is how the management of Equality B education in PKBM Harapan Bangsa, Kecamatan District Tambang , Kabupaten Kampar. This research was conducted at PKBM Harapan Bangsa, Tambang Subdistrict, Kampar Regency and involved 3 informants who were used as resource persons, including the manager as the core informant I, package B tutors as core informants II, and package B tutors as control informants. This research was conducted at PKBM Harapan Bangsa, Tambang Subdistrict, Kampar Regency and involved 3 informants who were used as resource persons, including the manager as the core informant I, package B tutors as core informants II, and package B tutors as control informants. Data collection techniques in this study were documentation, observation, and interview techniques. While the analysis in this study is data reduction, data display, and data verification. The results showed that the management of equality education package B implemented by managers included planning (organizing), organizing, actuating, and controlling activities found to be good because the managers paid attention to the series of management activities. The management of Equality Packet B education at PKBM Harapan Bangsa has been running well by the management of EQB, this can be seen from the existence of planning activities (planing) carried out by the Equality Packet education learning manager, the existence of organizing activities (organizing) such as the division of tasks of authority and responsibility responsible for the management of equality of package B, the actuating process in equality education of package B goes well can be seen from the implementation of the learning process and the fulfillment of the rights and obligations of the tutor and learning citizens. There was no evaluation of the implementation of the Equality Program B package, but it was seen from the UNBK results in the Equality Education Package B.Key Words: Management, Learning, Equality Education Package B